Effects of the arterial radius and the center-line velocity on the conductivity and electrical impedance of pulsatile flow in the human common carotid artery. - Shen, Hua; Li, Siqi; Wang, Yu; Qin, Kai-Rong (Medical & Biological Engineering & Computing, 2019)
In order to investigate the contribution of arterial radius and center-line velocity to the blood conductivity and electrical impedance of pulsatile flow in the human common carotid artery, we proposed three simplified mathematical models to describe the relationship between the center-line velocity, the arterial radius, and the blood conductivity. By comparing the fitting results with those obtained from our previously proposed elastic-tube hemodynamic model, we found that the change in center-line velocity had more notable effect on the blood conductivity than the change in arterial radius. Moreover, the change in arterial radius contributed much more to the electrical impedance than the change in blood conductivity induced by the center-line velocity. Graphical abstract Graphical abstract contains poor-quality text inside the artwork. Please do not re-use the file that we have rejected or attempt to increase its resolution and re-save. It is originally poor; therefore, increasing the resolution will not solve the quality problem. We suggest that you provide us the original format. We prefer replacement figures containing vector/editable objects rather than embedded images. Preferred file formats are eps, ai, tiff and pdf.The new graphical abstract have been attached. ᅟ.